Pemanfaatan Sampah Rumah Tangga Menjadi Beberapa Jenis Pupuk Cair MOL (Mikro Organisme Lokal) di Desa Pudak Kecamatan Kumpeh Ulu Kabupaten Muara Jambi - Rainiyati Rainiyati; Ahmad Riduan; Zulkarnain Zulkarnain; Eliyanti Eliyanti; Sarah Fiebrina Heraningsih (Universitas Mathla'ul Anwar Banten, 2019)
THE PROCESSING OF HOUSEHOLD WASTE INTO VARIOUS TYPES OF LOCAL MICRO ORGANISMS (LMO) LIQUID FERTILIZERS IN PUDAK VILLAGE, KUMPEH ULU DISTRICT, MUARO JAMBI REGENCY. Household waste such as leftover rice and vegetables can be used as a major component in producing Local Micro Organism (LMO). Local Micro Organism has many advantages, including being used as liquid organic fertilizer, as a decomposer in compost processing, as well as being used as bio-pesticides. The purpose of this community service project was to help the people, particularly farmers, in Pudak Village in producing LMO liquid fertilizer by providing them with relevant knowledge and technology. The technology was developed by utilizing of leftover rice and vegetables which are normally treated as unwanted household wastes. This LMO liquid fertilizer is very much needed by farmers to increase their farm output since it was proven to be able to improve plant growth and development, which in turn increase farm production eventually. In addition, this liquid fertilizer can also be sold and resulting in additional income for farmer household, and village community in general. Finally, as is stated in the objective, this community service program has produced output in the form of LMO liquid fertilizer, which then can be applied on farmers’ field.